Pharmacokinetics and tissue residues of an oxytetracycline/diclofenac combination in cattle - Mestorino, Olga Nora (2007)
Eight male cattle were given a combined dose containing 20 mg/kg oxytetracycline and 0.5 mg/kg diclofenac intramuscularly. Blood samples were drawn at different times until 168 h after administration. Two experimental animals were slaughtered by humane means at weekly intervals up to 28 days after administration. Samples of muscle, injection zone tissue, liver, kidney and fat were obtained. Oxytetracycline and diclofenac concentrations were determined by high performance liquid chromatography. Kinetic analysis was performed by linear regression using the CSTRIP programme. Plasma oxytetracycline concentration showed a maximum (Cmax) of 3.89 ± 1.48 μg/ml and a prolonged elimination half-life (T½b: 47.73 ± 18.33 h). The diclofenac plasma profile showed high Cmax (577.62 ± 238.40 ng/ml), and its T½b was also prolonged (30.48 ± 9.42 h). Oxytetracycline concentrations were measurable in liver and adipose tissue until day 21 after administration, but all tissue samples were negative for diclofenac at 21 days. The long elimination half-life of diclofenac was an unexpected finding; its T½b in humans is 1.1 h.